(untitled) (GESTIÓN Y TENDENCIAS, 2022)
Increasingly, and not before time, discussion of the sustainability of development has become part of the political, institutional, economic, social, and organizational spheres. However, the understanding of what a sustainable company is remains a work in progress and has often been mixed with different approaches, generating a degree of confusion. Given this, the article seeks to contribute to the discussion of what a sustainable company is by reviewing a series of related approaches, beginning with an analysis of the definition of sustainable development.